HIGH SENSITIVITY C-REACTIVE PROTEIN SHOWING INDEPENDENT RELATIONSHIP WITH PERIPHERAL VASCULAR ATHERSCLEROSIS AND WAIST CIRCUMFERENCE IN HEALTHY ADULTS - W.B.TREEBUPHACHATSAKUL; P.NGAMLERT (International Journal of Pharma and Bio Sciences, 2013)
This study investigated the associations among serum hs-CRP, peripheral vascular atherosclerosis, body mass index (BMI), and waist circumference (WC) in 347 healthy Thai adults. Overweight, obesity, central obesity, and peripheral vascular atherosclerosis occurs in healthy adults. Decreasing 0.1 of ABI and increasing 10 cm. of WC resulted in increasing of hs-CRP by 0.4 and 0.2 mg/L, respectively (R2 = 0.10, P = 0.013) while BMI could not be used to predict hs-CRP and vascular indexes in this study. Healthy adults with central obesity and having vascular atherosclerosis had hs-CRP (2.31 mg/L) higher than those (0.82 mg/L) without vascular atherosclerosis (P<0.001). In conclusions, a reduction in WC could be predicted in a reduction in hs-CRP and also a reduction in vascular atherosclerosis could be predicted when hs-CRP was decreased. Controlling WC and following serum hs-CRP may help guide preventive interventions to reduce future CVD in healthy Thai adults.